Toward Accelerating Deep Learning at Scale Using Specialized Hardware in the Datacenter - Ovtcharov, Kalin; Ruwase, Olatunji; Kim, Joo-Young; Fowers, Jeremy; Strauss, Karin; Chung, Eric (Proceedings of the 27th IEEE HotChips Symposium on High-Performance Chips (HotChips 2015), 2015)
This Talk: Are FPGAs a Promising Target in the Datacenter for Deep learning. A video of Eric Chung's presentation is available here.